The Effect of Indonesia Philanthropy’s Regulation Towards the Welfare State - Mukhlishin Mukhlishin; Khudzaifah Dimyati; Absori Absori; Jelang Ramadhan; Dinil Abrar Sulthani (BESTUUR, 2022)
Philanthropy has been very beneficial for social welfare. However, the regulation of philanthropy that governs philanthropy management institutions has not been successful in enhancing the welfare of the poor, particularly in post-COVID-19 tourism areas. This research explains the issue from a doctrinal normative perspective. The results indicate that the characteristics of philanthropy norms work as economic capital assistance, the regulation also should be able to identify the objectives and goals to be achieved for human welfare. Moreover, state and private institutions manage philanthropy independently, freely, and responsibly performing economic empowerment is developed with the existence of institutions that manage resources derived from philanthropic activities. These activities are based on the recommendations which are contained in scriptures and hierarchical juridical legitimacy containing transcendent norms.